The impact of Viral Marketing on Purchase Intention mediated by Consumer Behavior (Study on Tiktok User of Management Students at Bhayangkara Jakarta Raya University) - Ike Fitriani; Hadita Hadita; Dewi Puspaningtyas Faeni (Journal of Sustainable Community Development (JSCD), 2022)
This study aims to determine the impact of Viral Marketing on Purchase Intention mediated by Consumer Behavior (Study on Tiktok User Management Students at Bhayangkara Jakarta Raya University). This research is quantitative, with a sampling technique using non-probability sampling, that is, by using purposive sampling. Data were obtained through questionnaires which were distributed to 141 respondents. The data analysis technique in this study uses Partial Least Square using the SmartPLS 3.0 application. The results showed that: 1) Viral Marketing has a positive and significant influence on Purchase Intention, 2) Viral Marketing has a positive and significant influence on Consumer Behavior, 3) Consumer Behavior has a positive and significant influence on Purchase Intention, 4) Consumer Behavior can mediate Viral Marketing on Purchase Intention with full mediation